Celebrity advocacy in K-pop: social influence, religiosity, performance expectancy, and empathy as drivers of donation intention in the Jae Park–PRCF campaign - Saraun, Ferina Maria Arne; Setiyaningrum, Ari (Manajemen dan Bisnis, 2026)
This study examines the influence of social influence, religiosity, performance expectancy, and empathy on donation intention toward the Palestine Children’s Relief Fund (PCRF), promoted by celebrity Jae Park. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method via SmartPLS 3. The respondents were 180 millennials aged 29–44 who had seen Jae Park’s PCRF campaign on social media. The findings reveal that social influence and religiosity do not directly affect donation intention, whereas performance expectancy shows a significant positive effect. However, both social influence and religiosity significantly affect empathy, which in turn indirectly influences donation intention. Empathy functions as a full mediator between social influence and religiosity and donation intention, suggesting that empathy represents an important and compelling mediating variable to examine, given its essential role in motivating charitable behavior.